Respuesta :

Answer: A

Step-by-step explanation:

[tex]\frac{dy}{dx}=\frac{1+x}{xy} \\ \\ y \text{ } dy=\frac{1+x}{x} \text{ } dx \\ \\ y \text{ } dy= \left(\frac{1}{x}+1 \right) \text{ } dx \\ \\ \int y \text{ } dy=\int \left(\frac{1}{x}+1 \right) \text{ } dx \\ \\ \frac{y^{2}}{2}=\ln \left| x \right|+x+C[/tex]

Substituting in the initial condition,

[tex]\frac{(-2)^{2}}{2}=\ln \left|1 \right|+1+C\\\\2=1+C\\\\C=1[/tex]

So,

[tex]\boxed{\frac{1}{2}y^{2}=\ln \left|x \right|+x+1}[/tex]

Answer:

[tex]\textsf{A.} \quad \dfrac{1}{2}y^2=\ln|x|+x+1[/tex]

Step-by-step explanation:

To solve the differential equation:

Rearrange the given equation to get all the terms containing y on the left side, and all the terms containing x on the right side:

         [tex]\dfrac{dy}{dx}=\dfrac{1+x}{xy}[/tex]

[tex]\implies y\dfrac{dy}{dx}=\dfrac{1+x}{x}[/tex]

[tex]\implies y\:dy=\dfrac{1+x}{x}\:dx[/tex]

[tex]\implies y\:dy=\dfrac{1}{x}+\dfrac{x}{x}\:dx[/tex]

[tex]\implies y\:dy=\left(\dfrac{1}{x}+1\right)\:dx[/tex]

Integrate both sides:

[tex]\displaystyle \implies \int y\:dy=\int \left(\dfrac{1}{x}+1\right)\:dx[/tex]

[tex]\implies \dfrac{1}{2}y^2=\ln|x|+x+C[/tex]

Find the value of C using the given values of x and y:

when x = 1, y = -2

[tex]\implies \dfrac{1}{2}(-2)^2=\ln|1|+1+C[/tex]

[tex]\implies 2=0+1+C[/tex]

[tex]\implies C=1[/tex]

Substitute the found value of C:

[tex]\implies \dfrac{1}{2}y^2=\ln|x|+x+1[/tex]